2014
DOI: 10.1021/ic501278n
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and Spectroscopy of Anionic Cyclometalated Iridium(III)-Dithiolate and -Sulfinates—Effect of Sulfur Dioxygenation on Electronic Structure and Luminescence

Abstract: A new anionic heteroleptic Ir(III)-dithiolate complex Ir(ppy)2(benzene-1,2-dithiolate) (ppy = 2-phenylpyridine, [IrSS](-)) undergoes very fast air oxidation to form a monosulfinate complex [IrSSO2](-), which can be further dioxygenated by O2 or H2O2 to give a disulfinate complex [IrSO2SO2](-), which has been characterized by X-ray crystallography. The dioxygenation is accompanied by changes in the electronic structures of the complexes, leading to blue shift of emission from [IrSS](-) (λ(max) = 665 nm) to [IrS… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

7
43
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 22 publications
(50 citation statements)
references
References 100 publications
7
43
0
Order By: Relevance
“…The latter forms slightly puckered IrS 2 C 2 rings with IrS 2 −S 2 C 2 dihedral angle of 6.41°−27.64°, resulting from pyramidalization of the S atoms caused by the additions. 12 The OS bond lengths and stretching frequencies (1019 and 1149 cm −1 ) and OSO angle of the coordinated sulfinate in Figure S14 and Table S1) shows a puckered IrS 2 C 2 ring with IrS 2 −S 2 C 2 dihedral angle of 19.31°.…”
Section: For Selected Bond Lengths and Angles)mentioning
confidence: 98%
See 4 more Smart Citations
“…The latter forms slightly puckered IrS 2 C 2 rings with IrS 2 −S 2 C 2 dihedral angle of 6.41°−27.64°, resulting from pyramidalization of the S atoms caused by the additions. 12 The OS bond lengths and stretching frequencies (1019 and 1149 cm −1 ) and OSO angle of the coordinated sulfinate in Figure S14 and Table S1) shows a puckered IrS 2 C 2 ring with IrS 2 −S 2 C 2 dihedral angle of 19.31°.…”
Section: For Selected Bond Lengths and Angles)mentioning
confidence: 98%
“…Our previous DFT calculations showed that the optimized structure of [IrSS] − has C 2 symmetry (Figure 1). 12 The lowest unoccupied molecular orbital (LUMO) is a π* orbital of the ppy ligands, and the b 2 -symmetry highest occupied molecular orbital (HOMO) is an antibonding π* orbital arising from the interactions of the filled 3p y orbitals of the two thiolate S atoms (56.8%) with the filled 5d yz orbital of the Ir 3+ ion (11.95%) ( Figure 4) and is perpendicular to the C 2 axis. Viewing along the y-axis shows that for the Λ isomer, the lobes of the 3p y components (the lone pairs of the S atoms) in the HOMO on the re faces of both S atoms are blocked by the ortho-H atoms of the pyridyl rings, whereas the lone pairs on the si faces are fully exposed (Figure 3).…”
Section: For Selected Bond Lengths and Angles)mentioning
confidence: 99%
See 3 more Smart Citations